Competência profissional e assistência em anticoncepção Professional competence and contraceptive care - Escolástica Rejane Ferreira Moura; Raimunda Magalhães da Silva (Universidade de São Paulo, 2005)
OBJETIVO: Avaliar a competência técnica de profissionais que atuam no cuidado em anticoncepção. MÉTODOS: Realizou-se pesquisa do tipo avaliativa, na área da saúde, em oito municípios do Estado do Ceará, de julho a setembro de 2003. Os dados foram coletados mediante entrevistas com 29 enfermeiros e 50 usuários do Programa Saúde da Família e observações feitas nas unidades de saúde. RESULTADOS: A maioria dos enfermeiros havia participado de alguma capacitação sobre anticoncepção e normas técnicas. No entanto, foi relatada a existência de barreiras profissionais pelos enfermeiros e outras foram identificadas pelos usuários, os quais mostraram a necessidade de melhor capacitação dos profissionais que atuam nessa área. Os enfermeiros reconheceram dificuldades, tanto na comunicação e informação quanto técnicas, no manejo dos anticoncepcionais. CONCLUSÕES: Há lacunas na competência profissional em anticoncepção que associadas a falta de sistematização do trabalho em equipe, geram distorções na qualidade da atenção. O trabalho em equipe foi caracterizado pela indefinição de atribuições e tarefas dos seus membros. OBJECTIVE: To evaluate the technical competence of professionals carrying out activities related to contraceptive care. METHODS: Evaluative research in the field of health was conducted in eight districts of the State of Ceara from July to September 2003. Data was collected by means of interviews with 29 nurses working in the Family Health Care Program within these districts and 50 people being attended by this program. Observations of the Family Health Care Units were a complementary source of data within this study. RESULTS: The majority of nurses had received some form of training regarding contraception and the technical norms regulating their use. However, professional barriers were reported by the nurses and others were identified by lay persons being attended by the program, that indicate the need to provide better training for professionals engaged in this area of care. The nurses recognized they had deficits in information and communication skills as well as technical deficits in dealing with contraception. CONCLUSIONS: There are gaps in professional competence with regard to contraceptive care that, when associated to the lack of systematization of team work, generates distortions in the quality of care. Team work was characterized by the lack of definition of team members' specific attributions and tasks.